HUBUNGAN ANTARA KEPERCAYAAN DIRI DENGAN GANGGUAN KECEMASAN SOSIAL PADA MAHASISWA PROGRAM STUDI PENDIDIKAN DOKTER UNIVERSITAS NUSA CENDANA - Melati Savana Abdillah; Sidarta Sagita; Herman Pieter Louis Wungouw; Dickson Legoh (Cendana Medical Journal, 2025)
Background : Nowadays, a medical student is demanded to have an effective communication skill, in such a manner that a medical student is expected to be confident and be able to communicate well and effectively. Anxiety in medical student can come from the medical curriculum itself, way too many subjects for such limited time to study over. The high anxiety level in medical student may affect their academic result not representing their actual academic skill. Low confidence can lead to social anxiety that may cause negative effect to their lives. Aim : To discover the relation between confidence and social anxiety disorder in medical students of medical school of Nusa Cendana University. Method : The research method being used is observational analytic with case control progam which is conducted to the medical students of Nusa Cendana University by filling out Lauster Self Confidence questionnaire and Social Anxiety questionnaire by Dr. Cahyaning Suryaningrum. Using probability sampling and stratified random sampling technique with the total of 150 students who fit the criteria of inclusion. The bivariate analysis will be conducted using Somer's D correlation test. Result : From the total of 150 respondent, 75 students (50.0%) have high level of social anxiety and the other 75 students (50.0%) have low level of social anxiety. Moreover, 20 respondents (13.3%) are found to have very high level of confidence, 72 respondents (48.0%) have high level of confidence, 54 respondents (36.0%) have medium level of confidence, and 4 respondents (2.7%) have low level of confidence. Given he bivariate statistic test result is p = 0.00 which shows the significant relation between confidence and social anxiety disorder. Conclusion : Correlation is found between confidence level and social anxiety disorder in medical students of medical school, Nusa Cendana University. Keywords : Confidence Level, Social Anxiety Disorder, Medical Students in Kupang